Settlement experiences of recently arrived humanitarian migrants - Jenkinson, Rebecca; Silbert, Michelle; De Maio, John; Edwards, Ben (My University, 2016)
This fact sheet looks at the early settlement experiences of about 2400 humanitarian migrants who arrived in Australia in late 2013. Using Wave 1 data from the Building a New Life in Australia (BNLA) longitudinal study, it describes key aspects of migrants’ lives including their experiences of trauma, education, employment and housing.
Keywords: Life Events -- Immigration / newly arrived migrants; Disadvantage, adversity and resilience; Life Events; Immigration / newly arrived migrants; Adversity and resilience; Dsiadvantage, adversity and resilience